2007
DOI: 10.1080/10284150601153801
|View full text |Cite
|
Sign up to set email alerts
|

Plasma, red blood cells phospholipids and clinical evaluation after long chain omega-3 supplementation in children with attention deficit hyperactivity disorder (ADHD)

Abstract: Omega-3 and omega-6 long-chain polyunsaturated fatty acids (LCPUFAs), are crucial to brain development and function. Increasing evidence indicates that deficiencies or metabolic imbalances of these fatty acids might be associated with childhood developmental and psychiatric disorders including attention-deficit/hyperactivity disorder (ADHD). Omega-3 are often lacking on modern diets. Moreover preliminary evidences suggest that supplementation with omega-3 LCPUFAs, might help in the management of the ADHD linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 52 publications
0
48
0
Order By: Relevance
“…A study based in Italy showed that supplementing ADHD children with fish oil (rich in omega-3 fatty acids) is beneficial for their condition [95]. Both inattention and hyperactivity scores decreased after fish oil supplementation (13.90±4.01 and 15.50±4.41, respectively) compared to the scores before supplementation (19.00±4.20 and 20.00±4.18, respectively).…”
Section: Dementiamentioning
confidence: 98%
See 1 more Smart Citation
“…A study based in Italy showed that supplementing ADHD children with fish oil (rich in omega-3 fatty acids) is beneficial for their condition [95]. Both inattention and hyperactivity scores decreased after fish oil supplementation (13.90±4.01 and 15.50±4.41, respectively) compared to the scores before supplementation (19.00±4.20 and 20.00±4.18, respectively).…”
Section: Dementiamentioning
confidence: 98%
“…Increased ↑, higher levels after supplementation, as compared to baseline, before supplementation/placebo group; Decreased ↓, lower levels after supplementation, as compared to baseline, before supplementation/placebo group [95,96].…”
Section: Dementiamentioning
confidence: 99%
“…A standard mixture (Sigma-Aldrich) containing the major fatty acids was injected to identify sample peaks. 41 Proteomic experiments. MFGs were recovered as cream and oil in the supernatant layer and washed three times with 0.9% NaCl, and the associated proteins were extracted as described elsewhere.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…The methylester fatty acids were obtained with sodium methoxide in methanol, 3.33% w/v, and injected into an Agilent gas-chromatograph (HP 5890, series II plus, Agilent Technologies, Palo Alto, CA, USA), equipped with a flame ionization detector HP 7673 under the following experimental conditions: capillary column AT Silar (Alltech Associates, Deerfield, IL) (5% methyl polysiloxane) length 30 m, id 0.332 mm; film thickness 0.25 lm; gas carrier: helium, flow rate 5 mL/min; temperatures: injector 2508C, detector 2758C, oven 508C for 2 min, rate 108C/min until 2008C for 20 min. A standard mixture (Sigma -Aldrich) containing the major fatty acids was injected to identify sample peaks [25]. The statistical analysis was performed with the ANOVA test.…”
Section: Extraction and Analysis Of Fat Fractionsmentioning
confidence: 99%